Financial crises, liquidity, and the international monetary system - Tirole, Jean (Princeton University Press, 2002)
"Jean Tirole first analyzes the current views on the crises and on the reform of the international financial architecture. Reform proposals often treat the symptoms rather than the fundamentals, he argues, and sometimes fail to reconcile the objectives of setting effective financing conditions while ensuring that a country "owns" its reform program. A proper identification of market failures is essential to reformulating the mission of an institution such as the IMF, he emphasizes. Next he adapts the basic principles of corporate governance, liquidity provision, and risk management of corporations to the particulars of country borrowing. Building on a "dual- and common-agency perspective," he revisits commonly advocated policies and considers how multilateral organizations can help debtor countries reap enhanced benefits while liberalizing their capital accounts."--Jacket